MODEL- MODEL EVALUASI KURIKULUM - Ismail, Fajri (LPPM STKIP PGRI Bandar Lampung, 2014)
Curriculum as a set design that contains objectives, content / materials, media (infrastructure), learning strategies and processes continue to evolve to meet the challenge of science and technology and the needs of society. The curriculum requires rigorous evaluation to determine the educational improvement measures for the creation of a powerful output.Curriculum evaluation is an activity to give consideration and decision of all educational activities in the school such as students, teachers, models and methods of teaching, administration, facilities and infrastructure. There are two approaches of curriculum evaluation is qualitative and quantitative approaches. Quantitative model has a characteristic in which the collection of data by using a quantitative methodology and tests as a means of collecting data. While the qualitative model which departs from the philosophy of phenomenology is characterized by the evaluator as an important instrument in the main study.